Quality of Public Services in the field of Population Administration in Jatinangor District Sumedang Regency - Ramdani, Deni; Pauzi, Muhammad; Zarkasi (Decision, 2025)
This study focuses on the population administration services provided in Jatinangor District, Sumedang Regency. Its aims are to describe and analyze the quality of public services in the field of population administration, as well as to identify the factors that both support and hinder the implementation of these services. The research employs a qualitative descriptive method, utilizing observation, interviews, and documentation for data collection. The informants in this study included the Head of the Government Section of the Sub-district, the Sub-district Secretary, employees, and the community. The findings indicate that the quality of population administration services in Jatinangor District is quite good but not yet optimal. This is attributed to obstacles in the implementation of services that impede the completion of service products submitted by the community, as well as inadequate facilities in the service room and suboptimal cleanliness, leading to community discomfort